Catalogue of the primary types of marine molluscan taxa described by Tommaso Allery Di Maria, Marquis of Monterosato, deposited in the Museo Civico di Zoologia, Roma - Appolloni, Massimo; Smriglio, Carlo; Amati, Bruno; Lugliè, Lorenzo; Nofroni, Italo; Tringali, Lionello P.; Mariottini, Paolo; Oliverio, Marco (Zootaxa, 2018)
We have compiled a complete list of new marine molluscan taxa introduced by Tommaso Allery Di Maria, Marquis of Monterosato (1841–1927). The dates of publication of every single work have been checked against available evidence, and an updated bibliography is also presented. Finally, the type material of all marine taxa expected to be in the collection Monterosato (presently preserved in the Museo Civico di Zoologia in Rome) has been searched in the main collection, and all retrieved specimens have been catalogued. A large majority of the material has been found, representative specimens of each taxon have been illustrated, and remarks on nomenclature and taxonomy have been provided yielding 42 new synonymies, 46 nominal taxa rediscovered, and 6 new combinations.